Palaeomagnetic records of the Laschamp and Mono Lake geomagnetic excursions from Tongariro, New Zealand - Mazumdar, Adrija (2022)
Palaeomagnetic records of the Laschamp (LE, ∼41 ka) and Mono Lake (MLE, ∼33 ka) geomagnetic excursions have been discovered globally in volcanic and sedimentary records; however, records from the southern hemisphere are rare. This research presents new and revised direction and intensity estimates of characteristic remanent magnetization from 46 - 24 ka lavas from the Tongariro Volcanic Centre (TgVC) in the central North Island, addressing controversies regarding the age, duration, and global structure of the field, to understand features of excursions and the underlying geodynamo mechanism. Existing data from the TgVC and the Auckland Volcanic Field are combined with data from two new sites on Mt Tongariro and revised data from eight previously sampled sites on Mt Ruapehu, dated by 40Ar/39Ar methods. Palaeodirection results show evidence of reversed and intermediate polarity directions around ∼43 ka and ∼31 ka, lying within the accepted age ranges of the LE and MLE excursions. Palaeointensity estimates made using traditional Thellier-type methods yield anomalously low palaeointensities from three of four studied sites around the MLE and from a post-LE site. Additional Shaw-type experiments were conducted to test the efficacy of limiting heating to minimize thermal alteration. Results show an unequivocal record of both excursions in the central North Island, with strong support for full polarity reversals of the field during both excursions and decay of field strength to ∼20 - 30%. Mapping of virtual geomagnetic pole (VGP) positions for all North Island sites suggests that the field evolved through complex non-dipole field configurations during both events. However, a possible underlying dipolar control is indicated by an apparent favoured VGP longitude over the Americas that is identified in both excursions, separated by 10 ky. Support for this hypothesis is observed in the simple, wide, clockwise VGP loop proposed, and in the correlation of VGP positions across global datasets for both the MLE and LE. ...